Not Her Daughter - Frey, Rea (New York : St. Martins Griffin, 2018)
When a struggling mother loses her five-year-old daughter to a kidnapper, two women and one girl will find their loyalties and affections tested.
Keywords: Motherhood -- Fiction; Abandoned children -- Fiction; Missing children -- Fiction; Kidnapping -- Fiction; Child abuse -- Fiction; Thrillers (Fiction)